Comparative Study of Issuing Bankâs Obligations towards Beneficiary of the Letter of Credit under UCP and English Law - Alavi, Hamed (Hasanuddin University, 2016)
Process of international trade is complicated and risky. Risks will be more considerable when times come to deal with receiving/sending payments from/to unknown business partners in remote geographic areas. Employing documentary letters of credit (LC) is one of the ways to reduce payment risk in international business especially when partnerâs financial standing is unknown to each other. By using the LC as method of payment, parties will shift payment obligation from buyer as a natural person to the guarantee of bank as a legal person. The process of using LC is complicated and involves different players and relations between them. Amongst all relations in process of LC transaction, relation between issuing bank and beneficiary is the most complicated and least clear from legal stand point. This article tries to shed light on vague aspects of relations between issuing bank and beneficiary by studying obligations of the issuing bank towards beneficiary under the law of documentary letters of credit while comparing provisions of UCP with English Common Law on subject matter. Main objective of paper is providing answer to the question of what is the role of issuing bank in the process of LC transaction and which liabilities does it have towards beneficiary? Article consists of five main parts. Part one will provide an introduction to function and relation among different parties in process of an international LC transaction. Further, it endeavours to tap on principle of autonomy and strict compliance as governing principles of documentary letters of credit. Part two and three will take a comprehensive look at legal basis of relations between issuing bank and beneficiary, as well as bankâs obligations under documentary credit law. Part four will discuss liabilities of issuing banks towards beneficiary and finally part five will touch upon situation in which bank will right to recourse against beneficiary.